rút gọn phân thức : (x^2 / x^2) -(4 – x / x-2) + (2/ x+ 2)

rút gọn phân thức : (x^2 / x^2) -(4 – x / x-2) + (2/ x+ 2)

2 bình luận về “rút gọn phân thức : (x^2 / x^2) -(4 – x / x-2) + (2/ x+ 2)”

  1.  x^2/(x^2 – 4) – x/(x – 2) + 2/(x + 2)
    = x^2/(x^2 – 4) – (x^2 + 2x)/(x^2 – 4) + (2x – 4)/(x^2 – 4)
    = (x^2 – x^2 – 2x + 2x – 4)/(x^2 – 4)
    = -4/(x^2 – 4)

    Trả lời
  2. x^2/(x^2-4)-x/(x-2)+2/(x+2) (ĐKXĐ: x ne ±2)
    =x^2/((x-2)(x+2))-x/(x-2)+2/(x+2)
    =(x^2-x(x+2)+2(x-2))/((x-2)(x+2))
    =(x^2-x^2-2x+2x-4)/((x-2)(x+2))
    =(-4)/((x-2)(x+2))

    Trả lời

Viết một bình luận

Câu hỏi mới